2016
DOI: 10.1080/02508060.2016.1130910
|View full text |Cite
|
Sign up to set email alerts
|

Territorial pluralism: water users’ multi-scalar struggles against state ordering in Ecuador’s highlands

Abstract: Ecuadorian state policies and institutional reforms have territorialized water since the 1960s. Peasant and indigenous communities have challenged this ordering locally since the 1990s by creating multi-scalar federations and networks. These enable marginalized water users to defend their water, autonomy and voice at broader scales. Analysis of these processes shows that water governance takes shape in contexts of territorial pluralism centred on the interplay of divergent interests in defining, constructing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
26

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 44 publications
0
83
0
26
Order By: Relevance
“…Stern, Dietz, Dolsak, Ostrom, and Stonich (, p. 476) observed that movements “have asserted the right to participate in institutional design,” and could be crucial for both institutional functioning and innovation, because they are “linked across scale and place in ways which may help to spread design innovations.” (p. 476). There is ample evidence on how social movements can lead to policy changes that promote more ecological and just governance (e.g., Bullard & Johnson, ; Weldon, ; Htun & Weldon, ), to improved cross‐scale implementation of existing policies (e.g., Barnes, Lynham, Kalberg, & Leung, ; Hoogesteger, Boelens, & Baud, ), and to the strengthening of local commons governance (Villamayor‐Tomas & García‐López, ).…”
Section: From Polycentric Governance To Polycentric Strugglesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stern, Dietz, Dolsak, Ostrom, and Stonich (, p. 476) observed that movements “have asserted the right to participate in institutional design,” and could be crucial for both institutional functioning and innovation, because they are “linked across scale and place in ways which may help to spread design innovations.” (p. 476). There is ample evidence on how social movements can lead to policy changes that promote more ecological and just governance (e.g., Bullard & Johnson, ; Weldon, ; Htun & Weldon, ), to improved cross‐scale implementation of existing policies (e.g., Barnes, Lynham, Kalberg, & Leung, ; Hoogesteger, Boelens, & Baud, ), and to the strengthening of local commons governance (Villamayor‐Tomas & García‐López, ).…”
Section: From Polycentric Governance To Polycentric Strugglesmentioning
confidence: 99%
“…(p. 476). There is ample evidence on how social movements can lead to policy changes that promote more ecological and just governance (e.g., Bullard & Johnson, 2000;Weldon, 2011;Htun & Weldon, 2012), to improved cross-scale implementation of existing policies (e.g., Barnes, Lynham, Kalberg, & Leung, 2016;Hoogesteger, Boelens, & Baud, 2016), and to the strengthening of local commons governance (Villamayor-Tomas & García-López, 2017).…”
Section: Social Movements As Polycentric Arrangements and As Excludmentioning
confidence: 99%
See 1 more Smart Citation
“…Para analizar las socioecologías de las aguas subterráneas y la concentración de acceso a las aguas subterráneas es necesario un marco conceptual en capas. Este marco puede visualizarse como una cebolla, con un núcleo que consta de los conceptos para estudiar las redes hidrosociales (Wester, 2008) que constituyen la socioecología de las aguas subterráneas, es decir, las configuraciones de tecnologías, seres humanos, aguas subterráneas y otros recursos productivos y materiales dentro de un territorio determinado Hommes et al, 2018;Hoogesteger et al, 2016). La capa que rodea este núcleo interno consta de la economía política de las cadenas de productos básicos (agrícolas e industriales), las políticas agrarias y de mercado, así como de las políticas de gestión de acuíferos.…”
Section: La Injusticia Difusa (Los Colaterales)unclassified
“…As we show in this paper, for most Indigenous families and communities, water security is determined not just by absolute availabilities of water in their territories; most of all it is a function of historical and contemporary distribution patterns of resources and services (quantities and qualities), in a context of threats and encroachment practices (Babidge 2015;Hoogesteger and Verzijl 2015;Hoogesteger et al 2016;Saldías et al 2012;Zoomers 2010). This means that water security for one group of actors commonly entails water insecurity for others.…”
Section: Introductionmentioning
confidence: 99%